HYWALL CONTROLING SYSTEM” PENGAPLIKASIAN HYDROGELL KE DINDING PARTISI DENGAN TEKNOLOGI REMOTE CONTROL UNTUK MENGURANGI PENGGUNAAN AIR CONDITIONER PADA RUANGAN KANTOR - Diana Puspita Sari (Jurnal Proyek Teknik Sipil, 2020)
Geographically, Indonesia is a tropical country that has an average temperature characteristic of 35 ° C. Climatic conditions often make people feel uneasy because the hot air is felt even inside room so the use of air conditioner is very influential in creating a sense of comfort in the room, especially for work activities. However, the use of air conditioners is considered less friendly to the environment, because freon gas released into the air make thin the layers of earth's atmosphere. In addition to being less friendly to the environment, air conditioners are also less affordable for the community, even in offices with ample space, only one piece is installed which makes it less pronounced. The concept of Hywall Controling System is a technological concept is applied to partition walls with the main ingredient is Hydrogell. Hydrophilic gels or hydrogels are artificial polymers that have a degree of flexibility that is very similar to natural tissue and can absorb and release water 100-200 times its size and contain 90% water content. The hydrogell will be combined with the partition wall in the office room with running water using remote control technology so that the hydrogell will release water vapor which suppresses the condition of the hot air in the room and reduces the use of air conditioner.